The Role of Teachers in Addressing Bullying Behavior in Islamic Schools: Approaches and Best Practices in MAN 2 Lamongan - Liya Hidayah; Winarto Eka Wahyudi (J-PAI: Jurnal Pendidikan Agama Islam, 2025)
Bullying in educational institutions remains a prevalent issue in Indonesia, with significant cases reported across various levels of schooling. The Indonesian Child Protection Commission (KPAI) recorded over 810 child abuse cases in schools in 2023, with bullying being a major concern. One notable case involved a junior high school student in Sukabumi who lost their life due to physical bullying by peers. This study examines the role of Islamic Education teachers at MAN 2 Lamongan in addressing bullying, particularly through positive psychology, character building, and social-emotional learning. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving Islamic Education teachers, counseling staff, and students. The findings indicate that Islamic Education teachers play multifaceted roles as educators, counselors, motivator, role models and administrator. They implement anti-bullying strategies by incorporating Islamic values into lessons, conducting moral education, and fostering a supportive school environment. Despite these efforts, students reluctance to report bullying incidents remains a challenge. To enhance anti-bullying measures, schools should strengthen teacher training, increase the involvment of other stakeholders such as school staff or parents, and develop comprehensive policies that include digital literacy to combat cyberbullying. This study highlights the critical role of educators in creating a safe school atmosphere and suggests further research on intervention effectiveness in Islamic educational contexts.